HYDROTHERMAL SYNTHESIS OF ROD AND CHRYSANTHEMUM LIKE NANOSTRUCTURED ZnO - Anissa A. Putri; Tutik D. Wahyuningsih; Indriana Kartini (Indonesian Journal of Chemistry, 2011)
Rod and chrysanthemum-like nanostructured ZnO thin film have been prepared hydrothermally in NaOH and NH3 solution utilizing zinc nitrate hexahydrate as the precursor. ZnO thin films were grown on ITO glass substrate with the seed layer of zinc oxide. Perpendicularly aligned arrays of corrugated ZnO nanorods were grown in NaOH solution, while the chrysanthemum like structure was obtained in ammonia solution. X-Ray diffraction patterns confirmed that both morphologies presenting wurtzite crystal of ZnO. The nanorod showed strong (002) orientation of ZnO.